2017
DOI: 10.18632/oncotarget.19560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical utilities of the platelet count and platelet-lymphocyte ratio for predicting survival in patients with cervical cancer: a single institutional study and literature review

Abstract: ObjectiveTo compare the clinical utilities of the platelet count and platelet-lymphocyte ratio (PLR) for predicting survival in patients with cervical cancer.ResultsMultivariate analyses demonstrated that thrombocytosis and elevated PLR were found to be independent prognostic factors for progression-free survival (PFS, P = 0.0077, P = 0.044) and overall survival (OS, P = 0.025, P = 0.019) in separate Multivariate analyses. In the ROC analysis, the platelet count showed a significantly greater area under the RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 31 publications
(23 reference statements)
3
27
0
1
Order By: Relevance
“…Therefore, irradiation to the normal liver using the TomoHelical mode might lead to increases in TGF‐β1 and Treg number, decreasing the efficacy of DC‐based vaccine therapy. It was reported that the pretreatment NLR, MLR, and PLR were associated with the prognosis of patients with malignant solid tumors . In a systematic review and meta‐analysis, NLR greater than 4 was associated with the poor prognosis, and this was also the case in our study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, irradiation to the normal liver using the TomoHelical mode might lead to increases in TGF‐β1 and Treg number, decreasing the efficacy of DC‐based vaccine therapy. It was reported that the pretreatment NLR, MLR, and PLR were associated with the prognosis of patients with malignant solid tumors . In a systematic review and meta‐analysis, NLR greater than 4 was associated with the poor prognosis, and this was also the case in our study.…”
Section: Discussionsupporting
confidence: 84%
“…14 Palliative 3DCRT against the whole liver has also been used for multiple liver metastases in the past in Japan. Generally, the liver is sensitive to radiation and up to [30][31][32][33][34][35] Gy against the whole liver is considered to be the safe limit. 15 These doses are not high enough to obtain long-term control of liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with thrombocytosis had significantly poor OS and DFS of 41% and 39%, respectively at 5 years in our study. A similar trend was seen in all of the studies with chemoradiation (Table 3) (4,(10)(11)(12)16). The first study by Hernandez et al, in 1992, showed a 5-year-survival advantage of 65% in non-thrombocytosis versus 25% in patients with thrombocytosis.…”
Section: Discussionsupporting
confidence: 68%
“…Few studies on cervical cancer have assessed thrombocytosis as a prognostic indicator in patients receiving chemoradiation (5,(10)(11)(12)(13)(14)(15)(16). Two studies conducted by outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation